Jarum Sikenang (Semarang Keroncong Musicians Network) 2022: A Program for Promoting Cultural Advancement In Semarang - Ibnu Amar Muchsin (Universitas Negeri Semarang, 2024)
Keroncong is a distinctive Indonesian music genre regarded as a cultural heritage that needs preservation. However, keroncong music faces the threat of extinction, a concern shared by musicians, music enthusiasts, cultural experts, and government officials. This study aimed to identify and explain the establishment of “JARUM SIKENANG